2020
DOI: 10.3390/polym12061239
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric and Dielectric Study of Renewable Poly(hexylene 2,5-furan-dicarboxylate)-Based Nanocomposites In Situ Filled with Small Amounts of Graphene Platelets and Silica Nanoparticles

Abstract: Poly(hexylene 2,5 furan-dicarboxylate) (PHF) is a relatively new biobased polyester prepared from renewable resources, which is targeted for use in food packaging applications, owing to its great mechanical and gas barrier performance. Since both properties are strongly connected to crystallinity, the latter is enhanced here by the in situ introduction in PHF of graphene nanoplatelets and fumed silica nanoparticles, as well as mixtures of both, at low amounts. For this investigation, we employed Fourier transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 87 publications
2
30
0
Order By: Relevance
“…[poly(butylene furanoate) (PBF) and poly(hexylene furanoate) (PHF)] 4,16,18 . In principle the 4 polycondensation methods result in low molar mass PnAFs, which is the reason that in many cases PnAFs do not easily crystallize during cooling from the melt state, whereas they demonstrate quite strong cold crystallization during heating 5,19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[poly(butylene furanoate) (PBF) and poly(hexylene furanoate) (PHF)] 4,16,18 . In principle the 4 polycondensation methods result in low molar mass PnAFs, which is the reason that in many cases PnAFs do not easily crystallize during cooling from the melt state, whereas they demonstrate quite strong cold crystallization during heating 5,19 .…”
Section: Introductionmentioning
confidence: 99%
“…In our recent works 18,31,38,39 , we have demonstrated the potential for tuning the crystallizability of three furan based polyesters, namely, PPF, PBF and PHF, by reinforcing the polymer via the in situ introduction to the PnAF matrix of low amounts of various types nanoparticles acting as nucleating agents. The nanoparticles consisted of montmorillonite clays 40,41 , graphene nanoplatelets (GNP) and graphene oxide (GO) 42 , carbon nanotubes (CNT) 43 , halloysite nanotubes or spherical nanosilicas 44 .…”
Section: Introductionmentioning
confidence: 99%
“…One may assume that the kinetic fragility increases, along with cooperativity, by adding lignin to PLLA nanocomposites, due to the increase of the volume term; however, further investigations are needed to validate this assumption. Indeed, various trends can be found in the literature regarding fragility variations with nanofiller inclusion [ 24 , 50 , 57 , 58 , 59 ], and it has been shown that cooperativity and fragility can evolve in opposition [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is partly mitigated in FDCA-based polyesters with longer alkyl chains, as the higher molecular mobility helps the local ordered arrangement of the polymer chains, thereby favoring the obtainment of a relevant crystallinity degree [ 17 ]. This is desirable for the final applications, as a higher crystallinity degree is generally associated with a higher gas-barrier performance [ 22 ]. Moreover, an increased number of carbon atoms in the monomer diol leads to mitigation of the thermo-mechanical properties, i.e., a decrease in the elastic modulus, glass transition temperature, and melting temperature and an increase in flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…The existing studies mainly focus on the addition of carbon-based nanofillers and nanoclays in PEF [ 15 , 26 , 27 , 28 , 29 , 30 ], but some research also deals with PBF [ 31 ], poly(propylene furanoate) (PPF) [ 32 , 33 ], or poly(hexamethylene furanoate) (PHF) [ 22 ], mainly prepared by in-situ polymerization in presence of a nanofiller suspension. In these cases, nanofillers are added to increase the mechanical properties but especially the crystallization kinetics and the gas barrier performance [ 22 ]. Conversely, to the best of the authors’ knowledge, no research can be found on the development of nanocomposites with FDCA-based polymers with longer alkyl chains.…”
Section: Introductionmentioning
confidence: 99%